COLIFORM BACTERIAL POLLUTION IN RAWAL LAKE, ISLAMABAD AND ITS FEEDING STREAMS / RIVER - Mashiatullah, A.; Chaudhary, M. Z.; Khan, M. S.; Javed, T.; Qureshi, R. M. (The Nucleus, 2010)
Total coliform and fecal coliform are indicators of drinking water quality. The presence of fecal coliform in water indicates contamination with fecal materials of man and other animals. This paper documents the population of total coliform colonies as well as fecal coliform contamination in Rawal lake, which is one of major source of drinking water supply to inhabitants of Rawalpindi, and its feeding streams (mainly Kurang River and three perennial streams) flowing in the administrative jurisdiction of the capital city, Islamabad, Pakistan. Coliform bacteria in Rawal lake and feeding streams water was determined by membrane filtration technique. The results indicated that E. Coli population in four streams (input waters) feeding the Rawal Lake ranged from 25 - 57 (mean 36) fecal coliform per 100 mL. The Kurang River, one of the feeding streams, hosted the largest population of fecal coliform (57 fecal coliform per 100 mL). The highest population of fecal coliform (105 fecal coliform per 100 mL) in Rawal Lake surface water was observed at the confluence of Kurang River and the Lake in the vicinity of village â€œNew Amplerâ€. While in the Rawal Lake water columns, it ranged from 12 - 65 (mean 25) fecal coliform/ 100mL. The measured levels of fecal coliform bacteria are much higher than the maximum permissible levels for drinking water as recommended by WHO and US-EPA (No fecal coliform in drinking water). It is concluded that the indiscriminate amount of pollution from domestic sewage and poultry industry has seriously affected the biological quality of stream waters and the Rawal Lake waters.